A New Spectrophotometric Method for Hydrogen Sulphide Through Electrolytically Generated Mn(III) With O-Tolidine - M. S. Suresha; Mansour S. Abdul Galil; Mahadevaiah; M. A. Sathish; M. S. Yogendra Kumar; G. Nagendrappa (E-Journal of Chemistry)
A simple, sensitive and economical spectrophotometric method for the determination of hydrogen sulphide is developed. The method is based on a redox reaction in that Mn(III) generated electrolytically is taken in excess, which is oxidizing a known but a less quantity of hydrogen sulphide and the unreacted oxidant will oxidize further o-tolidine to produce an orange yellow quinonediimine absorbing cation (λ max. 455 nm). Therefore, in principle, the decrease in color intensity of the absorbing system is proportional to the concentration of hydrogen sulphide. The stoichiometry between Mn(III) and o-tolidine and stability constant of the complex were determined by Job's continuous method, the corresponding values were found to be 2:1 and 1.42X105 Lmol-1. The system was obeying Lambert-Beer's law in the range 0.2-1.4 μg mL-1 of hydrogen sulphide. Molar absorptivity, correlation coefficient and Sandell's sensitivity values were also calculated and found to be 4.2062X103 L mol-1 cm-1, 0.999 and 0.0012 μg cm-2 respectively. The method was employed for the determination of hydrogen sulphide in water samples. The results obtained were reproducible with acceptable standard deviation 0.01-0.068 and relative standard deviation, less than 3.21%. For a comparison, hydrogen sulphide present in water samples were also determined separately following the methylene blue official method. The results of the proposed method compare well with the official method.